Harmonisasi Pancasila, agama, dan negara dalam membangun identitas bangsa - Sobiro, Suhaillah (Maliki Interdisciplinary Journal, 2026)
Indonesia, as an archipelagic nation, embraces vast diversity in terms of ethicnity, culture, language, and religion. This diversity represents not only a source of strength but also a potential vulnerability when mis managed, as it may lead to identity conflics, discrimination, and intolerance. In this context, the harmonization of Pancasila, religion, and the state is essential to building a strong and sustainable national identity. Pancasila, as the state ideology, provides guidance for creating a just, civilized, and inclusive social order. Religion functions as a moral and spiritual foundation that directs society toward upholding human dignity and solidarity. Meanwhile, the state acts as a facilitator by guaranteeing freedom of religion, protecting citizens’ rights, and maintaining interfaith harmony. Globalization, modernization, and the rapid flow of information often challenge national unity, giving rise to extremism, materialism, and weakened social bonds. To address these challenges, this article proposes several solution: first, strengthening religious moderation that promotes tolerance and rejects violence; second, internalizing Pancasila values througt both formal and nonformal education, particulary targeting the younger generation as future nation builders; third, enhancing the state’s role as a facilitator of interreligious and intercultural dialogue to encourage constructive communication. Throught these strategies, Indonesia can establish a harmonious, inclusive, and adaptive national identity, capable of with standing the pressures of globalization while preserving unity amid diversity.